PTU-104 No surveillance or 5-year colonoscopy? the cost savings of discontinuing surveillance for low risk adenomas. (June 2019) - Shandro, Benjamin; Chang, Vincent; Mathur, Jai; O'Neill, Parker; Groves, Christopher; Sadler, Gareth; Poullis, Andrew
Abstract : Introduction: The benefit of colonoscopy surveillance for low risk adenomas (LRAs) is unclear. The BSG currently recommends either no surveillance or 5-year colonoscopy. It has recently been shown that following removal of LRAs, patients are not at increased risk of colorectal cancer compared to the general population. This suggests colonoscopy surveillance in these patients may not be necessary. In particular, patients aged 6–4 years when surveillance is due are eligible for biennial stool testing in the national bowel cancer screening programme (BCSP), which provides a potential alternative for follow up. We aimed to estimate the cost savings and endoscopy capacity that could be generated by discontinuing colonoscopy surveillance for LRAs. Methods: We conducted a retrospective endoscopy database analysis of patients for whom 5-year colonoscopy surveillance had been requested for LRAs between 2013 and 2018 at a London teaching hospital. Patients with inflammatory bowel disease, previous colorectal cancer or Lynch syndrome were excluded. The age at which colonoscopy surveillance was due was calculated. We calculated the annual cost savings and endoscopy capacity that could be generated for our trust by ceasing colonoscopy surveillance for LRAs in patients aged 6–4 years and in all patients, using the 2018 NHS tariff for diagnostic colonoscopy of £406. Results: 1035 patients were booked for colonoscopy surveillance for LRAs during the 5-year study period. 51.7% were male. The mean age at which colonoscopy surveillance was due was 63.5 years (SD 12.6). Discontinuing colonoscopy surveillance in patients aged 6–4 years with LRAs would save our trust £34, 997 per year and generate an additional 87 colonoscopy appointments per year. Discontinuing colonoscopy surveillance in all patients with LRAs would save our trust £84, 042 per year and generate an additional 207 colonoscopy appointments per year. Conclusions: Significant cost savings can be made, and endoscopy capacity generated, by discontinuing colonoscopy surveillance for LRAs. In the increasingly financially constrained NHS environment this approach should be explored, particularly in patients who are eligible for participation in the BCSP.